Quality of life changes and their predictors in young adult narcolepsy patients after treatment: A real-world cohort study - Chin, Wei-Chih; Wang, Chih-Huan; Huang, Yu-Shu; Hsu, Jen-Fu; Chu, Kuo-Chung; Tang, I; Paiva, Teresa (Frontiers in Psychiatry, 2022)
Background We conducted a five-year prospective follow-up study to track the real-world quality of life of patients with narcolepsy after medication and analyzed predictors. Methods The study ultimately included 157 participants who completed 5-year follow-up, 111 had type 1 narcolepsy (NT1) and 46 had type 2 narcolepsy (NT2). Polysomnography, multiple sleep latency test, actigraphy and HLA-typing were conducted. The Short Form 36 Health Survey Questionnaire (SF-36), the Stanford Center for Narcolepsy Sleep Inventory, the Epworth Sleepiness Scale (ESS), the visual analog for hypersomnolence (VAS), and Conners' Continuous Performance Test were used. Descriptive statistics, repeated measures, and hierarchical linear models were applied for analysis. Results Most demographic and clinical data did not significantly differ between groups, but the NT1 group had significantly more overweight, more severe narcoleptic symptoms, more positive HLA typing, shorter mean sleep latency, and more sleep onset rapid eye movement periods. No significant change to the physical domains of SF-36 was found in the total group, but we observed significant changes in emotional role functioning and social function. The NT1 group showed significant improvements in physical role functioning, emotional role functioning, and social function. The NT2 group demonstrated significant improvements in emotional role functioning. At the baseline, the NT2 group had significantly better scores, but there was no significant group difference after treatment, except for physical and social function. ESS and VAS were significantly improved during follow-up. At the baseline, the NT1 group had significantly higher ESS and VAS scores, and continuously significantly higher ESS scores during follow-up. Narcolepsy types, HLA typing, age of onset, symptom severity, attention and vigilance were significantly correlated with SF-36. Conclusion Symptom control greatly associates with the quality of life in narcoleptic patients, and medication can play the most important role. Management targeting narcoleptic symptoms, attention impairment, and drug adherence should be provided.